Differences in lobed gland structure and distribution in terrestrial isopods (Oniscidea) - Natasha Chipanovska; Vera Župunski; Miloš Vittori (Nauplius)
Abstract Lobed tegumental glands are found only in terrestrial isopods and are thought to have evolved in response to challenges associated with life on land. By examining 30 terrestrial isopod species, we aimed to determine the factors that influence the structure and distribution of the lobed glands. We discovered that lobed glands are found not only in the lateral plates and the uropods but also in the cephalothorax, the antennae, the tergites, and the pereopods of some species. The structure of the lobed glands is influenced by the phylogenetic position of an isopod. Namely, species of Diplocheta, Microcheta, and Synocheta have only one nucleus in the secretory cell, while two nuclei occur in the secretory cells of Crinocheta. By contrast, the distribution of the lobed glands in the body is influenced by the eco-morphotype of a species. Clingers and runners have numerous large lobed glands throughout the body. Creepers possess well-developed uropod glands, while lobed glands are absent or small and few in number in their pereon. Rollers have fewer lobed glands and some species apparently lack them. We also showed that several species possess several types of lobed glands. The correlation of lobed gland distribution with the eco-morphotype speaks in favor of the proposed defensive function of lobed glands.